2013
DOI: 10.1016/j.rboe.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cruciate ligament injury: characteristics and associations of most frequent injuries

Abstract: Objective To investigate the prevalence and combinations of PCL injuries and their correlations with the mechanism, the occurrence of evident dislocation and associated fracture. Method A retrospective study of 85 lesions of PCL operated between 2003 and 2010. Diagnosis by physical examination and dynamic radiography, compared with surgical findings. Results Injuries involving the PCL were more prevalent in men (78.8%) with a mean age of 33 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…In Malaysia, Che Ahmad et al 6 revealed that 67% of the patients with PCL tear sustained motor vehicle accidents. According to Caldas et al 7 and Schulz et al 8 motor vehicle accidents were the leading factor for isolated and combined PCL injuries which accounted for 78.8% and 45% of their cohort. On the other hand, Bernhardson et al 9 suggested that 78% of the patients suffered the PCL injury as a results of trauma due to sports event.…”
Section: Discussionmentioning
confidence: 98%
“…In Malaysia, Che Ahmad et al 6 revealed that 67% of the patients with PCL tear sustained motor vehicle accidents. According to Caldas et al 7 and Schulz et al 8 motor vehicle accidents were the leading factor for isolated and combined PCL injuries which accounted for 78.8% and 45% of their cohort. On the other hand, Bernhardson et al 9 suggested that 78% of the patients suffered the PCL injury as a results of trauma due to sports event.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in agreement with previous studies reporting a higher incidence of various concomitant injuries in a population with PCL injuries, whereas ACL injuries tend to occur either in isolation or in conjunction with meniscal lesions [ 8 , 24 ]. Furthermore, the higher occurrence of concomitant injuries in PCL-injured populations has previously been attributed to high-energy injury mechanisms, leading to more complex patterns of knee ligament injuries [ 7 , 8 , 35 ]. In line with previous research, [ 3 , 8 , 9 , 27 ], a high rate of traffic- and sports-related injury mechanisms has been reported in the population with a PCL injury, while ACL injuries most commonly occurred due to sports-related activities, especially pivoting sports.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior cruciate ligament (PCL), as the strongest ligament in the knee joint, is the most important joint structure to maintain the stability of the knee joint and occupies an important proportion in knee joint injury [1]. PCL injury will lead to the destruction of the knee joint's backward stability and rotation stability, seriously affecting the physiological function of the affected lower limbs, and greatly reducing the quality of life of patients [2].…”
Section: Introductionmentioning
confidence: 99%